Use of split‐free nano‐liquid chromatography–mass spectrometry/high resolution mass spectrometry interface to improve the detection of α‐cobratoxin in equine plasma for doping control. Issue 5 (25th January 2018) - Bailly‐Chouriberry, Ludovic; Garcia, Patrice; Cormant, Florence; Loup, Benoit; Popot, Marie‐Agnès; Bonnaire, Yves
Abstract: Cobra ( Naja naja kaouthia ) venom contains a toxin called α‐ cobratoxin ( α‐ Cbtx) containing 71 amino acids (MW 7821 Da) with a reported analgesic power greater than morphine. In 2013, the first analytical method for the detection of α‐ Cbtx in equine plasma was developed by Bailly‐Chouriberry et al, allowing the confirmation of the presence of α‐ Cbtx at low concentrations (1–5 ng/mL or 130–640 fmol/mL) in plasma samples. To increase the method sensitivity and therefore to improve the detection of α‐ Cbtx in post‐administration plasma samples, a nano‐liquid chromatography–mass spectrometry/high resolution mass spectrometry (nLC–MS/HRMS) method was developed. This new method allowed us to confirm the presence of α‐ Cbtx in plasma samples spiked at 100 pg/mL (12.8 fmol/mL) and the detection of α‐ Cbtx was obtained in plasma samples collected 72 hours post‐administration (50 pg/mL or 6.4 fmol/mL) which was defined as the limit of detection (LOD). The presented method is 20‐fold more sensitive compared to the method previously described. Abstract : A new analytical method based on nanoLC hyphenated to high resolution mass spectrometry is proposed to horse doping control laboratories in order to improve the detection of α‐cobratoxin in equine plasma.